2021
DOI: 10.3390/jmse9080911
|View full text |Cite
|
Sign up to set email alerts
|

Does Sand Beach Nourishment Enhance the Dispersion of Non-Indigenous Species?—The Case of the Common Moon Crab, Matuta victor (Fabricius, 1781), in the Southeastern Mediterranean

Abstract: Sand beach nourishment (BN) is one of the commonest “soft solutions” for shore protection and restoration. Yet it may have ecological consequences. Can this practice enhance the introduction and dispersal of non-indigenous species (NIS)? There has been little research on the impacts of nourishment on NIS, especially in the southeastern Mediterranean, a region considered most affected by invading biota. However, so far only one study referred to the possible interaction between BN and the success of invading sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Nourishments may also have ecological consequences. This Special Issue presents a study referring to the possible interaction between nourishments and the success of invading species [12]. It is suggested that direct communication between environmental regulators and scientists is crucial for improving both scientific research and environmental management policies [12].…”
mentioning
confidence: 99%
“…Nourishments may also have ecological consequences. This Special Issue presents a study referring to the possible interaction between nourishments and the success of invading species [12]. It is suggested that direct communication between environmental regulators and scientists is crucial for improving both scientific research and environmental management policies [12].…”
mentioning
confidence: 99%